Contributions of dermatologists to COVID‐19 research: A brief systematic review. Issue 4 (2nd July 2020) - Wang, Yuanzhuo; Fang, Rouyu; Zhang, Hanlin; Tang, Keyun; Sun, Qiuning
Abstract: Coronavirus disease 2019 (COVID‐19) has been declared a pandemic. We conducted a systematic review to reveal the contribution of dermatologists in COVID‐19 research. Two hundred and ninety‐eight articles were included and classified into cutaneous manifestations of COVID‐19, operating experience against COVID‐19, mechanisms and treatment of COVID‐19, disinfection and personal protective equipment (PPE)‐related skin diseases, and other topics. The value of these articles and their impact on clinical impact were discussed and we hope that dermatologists can have a better understanding of these areas from this study.